Visual disturbances in man as a result of experimental and occupational exposure to dimethylethylamine. Issue 1 (January 1991) - Ståhlbom, B; Lundh, T; Florén, I; Akesson, B
Abstract : Experimental exposure of four volunteers to 40-50 mg/m3 of dimethylethylamine (DMEA) for eight hours caused irritation of the mucous membrane of their eyes, subjective visual disturbances (haze), and slight oedema of the corneal epithelium. The thickness of the cornea showed a slight but consistent increase in all four subjects at these exposures and in two subjects exposed to 10 mg/m3. Concentrations of 80 and 160 mg/m3 for 15 minutes caused eye irritation but no visual disturbances or corneal oedema. Occupational exposure for eight hours to about 25 mg/m3 of DMEA (with peaks above 100 mg/m3) was also associated with eye irritation, haze, and corneal oedema. The divergence between our findings and other reports in which visual disturbances occurred at lower concentrations during occupational exposure may be due to peak concentrations.